Diagnóstico participativo do Nexus água-energia-alimento em comunidades rurais e ribeirinhas na Amazônia Oriental - Tavares, Gislleidy Uchôa (2022)
The nexus concept is applied in many global contexts to generate comprehension on the relationships between the water, food and energy sectors and to enhance investigations that aim to improve the living conditions of marginalized communities. Nexus studies are incipient and founded mostly on “top-down” quantitative methodologies, utilizing a national scale, with few examples of participatory and collaborative approaches. In this context, there emerges a need to understand with more precision, in an integrated and participatory manner, the water-food- energy nexus using “bottom-up” approaches, meaning that it is fundamental to question how the affected communities understand the relationship between these elements. Thus, we applied quali-quantitative methodologies to determine the nexus of rural and river communities of the Paraense Northeast, the community of Ponta do Urumajó, located in the municipality of Augusto Corrêa and the community of Arimbu, located in the municipality of Bragança. The technical-methodological procedures utilized in the development of the research were: (a) SWOT Methodology together with university extension activities to raise and debate issues on water, food and energy and (2) Q Method to analyze the subjectivity of the community managers in relation to the nexus. Applying the SWOT Methodology, we observed the social, economic, and environmental characteristics of the communities, as well as the population’s way of life. By means of the application and analysis of the Q Method, it was possible to identify the distinction of four subjectivities: Factor 1 (Income-Water Nexus); Factor 2 (Threats-Aid Nexus); Factor 3 (Food-Water Nexus); and Factor 4 (Aid-Rains Nexus), as well as the convergence and divergence points between these factors. Thus, we identified the interconnections of the nexus sectors within both communities, presenting results that differed from “top-down” approaches. Furthermore, some guidelines aimed at a more inclusive and sustainable nexus governance are indicated. Therefore, this work fills the relevant gaps in the Pará nexus, where these studies continue to be lacking and treat the nexus holistically in its water-food-energy triad, using a participatory, integrative and “bottom-up” approach.